THE EFFECT OF PROJECTS BASED LEARNING MODELS WITH ECOBRICKS ON PROCESS SKILLS IN PRIMARY SCHOOLS - Hasan, Rosdiana; Kune, Syarifuddin; Rahmawati, Rahmawati (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2023)
The study's objective was to examine how the Project Based Learning Model affected the scientific literacy and learning outcomes of class IV SDI Hombes Armed, Gowa Regency students with regard to the concept of energy sources. This kind of study makes use of desalin Desalin is the non-equivalent control group. There were 60 samples in total for this study, with 30 individuals in the experimental class and 30 in the control group. A learning achievement test was used to measure learning outcomes, questions about scientific literacy were used to assess scientific literacy skills, and documentation was also used. Descriptive statistical methods, inferential analysis, and hypothesis testing are the data analysis techniques employed. The Malcal 0,000 0,05 Manova hypothesis test resulted. The conclusion that there was an impact on the learning model of Project Balsed Learning on copy literacy abilities and student learning outcomes in the first place on the learning of IPAl class IV SDI Hombes Alrmed led to Ho's rejection in terms of acceptance. Therefore, it can be said that learning with the project-balanced learning model has an impact on students' learning outcomes in the class IV SDI Hombes Alrmed material related to the concept of energy sources as well as their scientific literacy abilities.